2019
DOI: 10.1007/jhep10(2019)282
|View full text |Cite
|
Sign up to set email alerts
|

Classifying 5d SCFTs via 6d SCFTs: arbitrary rank

Abstract: According to a conjecture, all 5d SCFTs should be obtainable by rankpreserving RG flows of 6d SCFTs compactified on a circle possibly twisted by a background for the discrete global symmetries around the circle. For a 6d SCFT admitting an F-theory construction, its untwisted compactification admits a dual M-theory description in terms of a "parent" Calabi-Yau threefold which captures the Coulomb branch of the compactified 6d SCFT. The RG flows to 5d SCFTs can then be identified with a sequence of flop transiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
182
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(185 citation statements)
references
References 30 publications
2
182
0
1
Order By: Relevance
“…First, one should understand the compactification of the 6d SCFTs on a circle to five dimensions. A lot of progress have been made on this front in recent years [16,22,23,29,30,44,[47][48][49][50][51][52][53][54][55][56][57][58]. In case the five dimensional theory has a gauge theory effective description it teaches us about the punctures we can have and how to glue four dimensional theories together.…”
Section: Discussionmentioning
confidence: 99%
“…First, one should understand the compactification of the 6d SCFTs on a circle to five dimensions. A lot of progress have been made on this front in recent years [16,22,23,29,30,44,[47][48][49][50][51][52][53][54][55][56][57][58]. In case the five dimensional theory has a gauge theory effective description it teaches us about the punctures we can have and how to glue four dimensional theories together.…”
Section: Discussionmentioning
confidence: 99%
“…We will not consider the former as they give rise to "decoupled states" [74,92] that decouple in the SCFT limit, and moreover, the partition function including such states do not preserve the G F flavor symmetry [92]. The latter, which we refer to as (0)-curves give rise to the spin 1 BPS states of the SCFT.…”
Section: M2-branes Wrapping Genus Zero Curves With Normal Bundlementioning
confidence: 99%
“…Another motivation to study these theories at present is recent progress in 6d SCFTs, where it is believed that a full classification of all UV-complete supersymmetric theories exists [4][5][6][7]. Indeed, recent works [1,2,[8][9][10][11][12][13][14] have suggested that all 5d N = 1 UVcomplete theories arise from appropriate circle reductions, possibly with holonomies for the global symmetries of 6d theories, thus conjecturing a classification of 5d theories.…”
Section: Introductionmentioning
confidence: 99%